THE STRUCTURE AND TERRITORIAL DYNAMIC OF FOREIGN DIRECT INVESTMENT IN ROMANIA - LILIANA SCUTARU (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2015)
This paper analyzes the structure of foreign direct investment in Romania, FDI agglomeration areas at the local level and their fields, with a particular analysis on greenfield investments because this type of investment is, par excellence, the promoter of new technologies and technical and technological progress. In this respect, the paper considers the analysis of foreign direct investment stock in greenfield enterprises and their location and territorial distribution by regions in Romania of stock of greenfield investments. The research reveals that, in the period under review, greenfield investments in Romania have shifted from the manufacturing sector to the service sector, thereby increasing the country's vulnerability to financial risks and speculation worldwide. In terms of regional distribution, the research highlights the fact that FDI are highly unevenly localized in Romania